The Impact of Human Resource Accounting on Enhancing Job Loyalty among Individuals Working in The Personnel Department - Weam Wahhab Abdul Hussein (Research Parks Publishers, 2026)
This study aimed to analyze the impact of human resource accounting on enhancing job loyalty among employees in the personnel department. A qualitative descriptive approach was used, and the study was conducted within the personnel department of the human resources division. The study investigated the extent to which human resource accounting practices and continuous performance evaluation affect employees' sense of loyalty. The results showed that human resource accounting plays a significant role in enhancing job loyalty by providing fair and transparent performance evaluation, which strengthens employees' sense of fairness and belonging to the organization. The results also indicated that employees who undergo regular accountability feel more confident in their work environment and demonstrate greater commitment to the organization's goals. The study recommends adopting modern human resource accounting methods and developing integrated training strategies to contribute to enhancing job loyalty and increasing overall employee satisfaction.